A Study to Evaluate Sevoflurane With or Without Nitrous Oxide and to Compare It with Propofol as Induction Agent- A Randomized Clinical Trial - Supratim Dasgupta; Babita Agrawal; Priyadershini Rangari (Academia Anesthesiologica International, 2019)
Background: All intravenous anaesthetic agents have drawbacks which are related to the particular agent used; though common to all is danger of loss of control of airway. Volatile agents are not suitable for gaseous induction as they are irritating to the airways. Sevoflurane is suitable for inhalational induction because of its low blood gas solubility and its non irritant effect on airways even in high concentration. Objectives: To evaluate sevoflurane with addition of 63% nitrous oxide for induction in adults, and to compare sevoflurane (with or without nitrous oxide) with Propofol as induction agent.Subjects and Methods: A total of one hundred and fifty patients of age between 20-40 years were taken and divided into three groups of fifty each. In group I, patients were induced with sevoflurane 8% in oxygen in group II, patients were induced with sevoflurane (8%) with 63% N2O in O2 and in group III, induction was carried out with Propofol.Results: Mean time of loss of eyelash reflex and jaw relaxation was statistically significant in all groups. The presence of breath holding amongst all the three groups found to be significant. The difference in oxygen saturation was not significant between group I and II but significant in group II and III. The slightly slower induction time with sevoflurane as compared to Propofol can be offset by reduced incidence of breath holding and involuntary movements.Conclusion: From this study it can be concluded that 8% sevoflurane carried in nitrous oxide and oxygen is a rapid, reliable and safe method for the induction of anaesthesia when a vital capacity technique is used.